Role of Education in Women Entrepreneurship Development In Nepal - Sigdel, Minu (Tribhuvan University Journal, 2016)
Men and women both experience personal problems during the startup of a business but women face more. This is especially true due to the lack of self-confidence and not being taken seriously by the fund providers when applying for funds. Relative to men, women tend to have lower access to land, education and training facilities. Thus, this study aims to study the ground realities of educational status of women entrepreneurs in the Kathmandu valley and to assesses the impact of education on their choice of business, their preferred legal ownership method, their means of obtaining funds and their means of getting support to initiate business.